Biological nitrogen fixation potential by soybeans at two lowP soils of southern Cameroon - Jemo, M.; Nolte, C.; Tchienkoua, M.; Abaidoo, Robert C. (Springer, 2010)
Biological nitrogen fixation (BNF) potential of 12 soybean genotypes were evaluated in condition of low and sufficient supply in two acid soils of southern Cameroon. The P sources were Togolese phosphate rock (PR) and triple super phosphate (TSP). The experiment was carried out during two consecutive years (2001 and 2002) at two locations with different soil types. Shoot dry matter, nodule dry matter, N and P uptake were assessed at flowering and the grain yield at maturity. Shoot dry matter, nodule dry matter, N and P uptake, and grain yield significantly varied with site and genotypes (P < 0.05). On Typic Kandiudult soil, nodule dry matter ranged from 0.3 to 99.3 mg plant-1 increasing significantly with P application (P < 0.05). Total N uptake of soybean ranged from 38.3 to 60.1 kg N ha-1 on Typic Kandiudult and from 18 to 33 kg N ha-1 on Rhodic Kandiudult soil. Under P limiting conditions, BNF ranged from -5.8 - 16 kg N ha-1 significantly higher values for genotype TGm 1511 irrespective of soil type. Genotype TGm 1511 can be considered as an important companion crop for the development of smallholder agriculture in southern Cameroon.